Gene and Transposable Element Expression Evolution Following Recent and Past Polyploidy Events in Spartina (Poaceae) - Giraud, Delphine; Lima, Oscar; Rousseau-Gueutin, Mathieu; Salmon, Armel; Aïnouche, Malika (Frontiers in Genetics, 2021)
Gene expression dynamics is a key component of polyploid evolution, varying in nature, intensity, and temporal scales, most particularly in allopolyploids, where two or more sub-genomes from differentiated parental species and different repeat contents are merged. Here, we investigated transcriptome evolution at different evolutionary time scales among tetraploid, hexaploid, and neododecaploid Spartina species (Poaceae, Chloridoideae) that successively diverged in the last 6-10 my, at the origin of differential phenotypic and ecological traits. Of particular interest are the recent (19th century) hybridizations between the two hexaploids S. alterniflora (2n=6x=62) and S. maritima (2n=6x=60) that resulted in two sterile F1 hybrids: S. x townsendii (2n=6x=62) in England and S. x neyrautii (2n=6x=62) in France. Whole genome duplication of S. x townsendii gave rise to the invasive neo-allododecaploid species S. anglica (2n=12x=124). New transcriptome assemblies and annotations for tetraploids and the enrichment of previously published reference transcriptomes for hexaploids and the allododecaploid allowed identifying 42,423 clusters of orthologs and distinguishing 21 transcribed transposable element (TE) lineages across the seven investigated Spartina species. In 4x and 6x mesopolyploids, gene and TE expression changes were consistent with phylogenetic relationships and divergence, revealing weak expression differences in the tetraploid sister species S. bakeri and S. versicolor (< 2 my divergence time) compared to marked transcriptome divergence between the hexaploids S. alterniflora and S. maritima that diverged 2-4 mya. Differentially expressed genes were involved in glycolysis, post-transcriptional protein modifications, epidermis development, biosynthesis of carotenoids. Most detected TE lineages (except SINE elements) were found more expressed in hexaploids than in tetraploids, in line of their abundance in the corresponding genomes. Comparatively, an astonishing (52%) expression repatterning and deviation from parental additivity were observed following recent reticulate evolution (involving the F1 hybrids and the neo-allododecaploid S. anglica), with various patterns of biased homoeologous gene expression, including genes involved in epigenetic regulation. Downregulation of TEs was observed in both hybrids and accentuated in the neo-allopolyploid. Our results reinforce the view that allopolyploidy represents springboards to new regulatory patterns, offering to worldwide invasive species, such as S. anglica, the opportunity to colonize stressful and fluctuating environments on saltmarshes.